If
∫ 0 1 x 2 0 1 6 ( x 2 0 1 6 + 1 0 0 8 ) ( x 2 0 1 6 + 2 0 1 6 ) 1 / 2 0 1 6 d x = c a 1 / b
where a , b , c are positive integers, a is not a multiple of perfect b th power.
Then find b + c − a .
Bonus: Generalize ∫ x n ( x n + d ) ( x n + 2 d ) 1 / n d x .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Short and sweet. I love this problem. I took some time to think about the first substitution.
Consider ,
∫ x n ( x n + d ) ( x n + 2 d ) n 1 d x
it can be rewritten as,
∫ x n − 1 ( x n + d ) ( x 2 n + 2 d x n ) n 1 d x
now let , t d t = x 2 n + 2 d x n = 2 n x 2 n − 1 + 2 n d x n − 1 = 2 n × x n − 1 ( x n + d )
The given integral becomes,
2 n 1 ∫ t n 1 d t = 2 n ( n 1 + 1 ) t n 1 + 1 + C = 2 ( n + 1 ) ( x 2 n + 2 d x n ) n 1 + 1 + C = 2 ( n + 1 ) x n + 1 × ( x n + 2 d ) n 1 + 1 + C
∫ 0 p x n − 1 ( x n + d ) ( x 2 n + 2 d x n ) n 1 d x = 2 ( n + 1 ) p n + 1 × ( p n + 2 d ) n 1 + 1
in the above problem n = 2 0 1 6 , d = 1 0 0 8 and p = 1 ,on simplifying we get
I = 4 0 3 4 1 × 2 0 1 7 2 0 1 6 1 + 1 = 2 1 × 2 0 1 7 2 0 1 6 1
⇒ a = 2 0 1 7 , b = 2 0 1 6 , c = 2
b + c − a = 2 0 1 6 + 2 − 2 0 1 7 = 1
Since x n ( x n + d ) ( x n + 2 d ) n 1 = 2 1 [ x n ( x n + ( x n + 2 d ) ) ( x n + 2 d ) n 1 ] = 2 1 [ x 2 n ( x n + 2 d ) n 1 + x n ( x n + 2 d ) n n + 1 ] = 2 1 [ x n + 1 × x n − 1 ( x n + 2 d ) n 1 + x n × ( x n + 2 d ) n n + 1 ] = 2 ( n + 1 ) 1 d x d [ x n + 1 ( x n + 2 d ) n n + 1 ] we have ∫ 0 1 x n ( x n + d ) ( x n + 2 d ) n 1 d x = 2 ( n + 1 ) 1 ( 2 d + 1 ) n n + 1 Putting n = 2 d we obtain 2 1 ( 2 d + 1 ) 2 d 1 , making the answer 2 d + 2 − ( 2 d + 1 ) = 1 .
Yeah, that serves the title best. Neat!
Problem Loading...
Note Loading...
Set Loading...
Proposition
∫ x n ( x n + d ) ( x n + 2 d ) 1 / n d x = 2 ( n + 1 ) 1 x n + 1 ( x n + 2 d ) 1 / n
Proof
Put x n + d = t ,
= n 1 ∫ ( t − d ) 1 / n t ( t + d ) 1 / n d t
= n 1 ∫ t ( t 2 − d 2 ) 1 / n d t
Put t 2 − d 2 = u n ,
= ∫ 2 u n d u
= 2 ( n + 1 ) u n + 1
= 2 ( n + 1 ) x n + 1 ( x n + 2 d ) 1 / n + 1